Avian influenza in Africa. Targeting vigilance - Visscher, Marie-Noël; Chevalier, Véronique; Gaidet-Drapier, Nicolas (Perspective, 2011)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"In 2006, the detection of the avian influenza (flu) H5N1 virus in Africa caused great concern: the virus could spread to the whole continent, and then be reintroduced to Europe by migratory birds. Epidemiological surveillance programmes were set up and national mechanisms strengthened with the support of international organisations. At the same time, research programmes were launched to describe and understand the virus transmission processes in Africa, and to assess the risks. Among these programmes, the GRIPAVI project is aimed at characterising the circulation of avian influenza viruses and Newcastle disease in both wild birds and domestic poultry. It shows that the African continent is not free from risk and that vigilance should continue. By specifying the virus persistence mechanisms in Africa and identifying risk situations, it proposes avenues for targeting surveillance and control strategies and thereby making them more efficient."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">English version of the article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"In 2006, the detection of the avian influenza (flu) H5N1 virus in Africa caused great concern: the virus could spread to the whole continent, and then be reintroduced to Europe by migratory birds. Epidemiological surveillance programmes were set up and national mechanisms strengthened with the support of international organisations. At the same time, research programmes were launched to describe and understand the virus transmission processes in Africa, and to assess the risks. Among these programmes, the GRIPAVI project is aimed at characterising the circulation of avian influenza viruses and Newcastle disease in both wild birds and domestic poultry. It shows that the African continent is not free from risk and that vigilance should continue. By specifying the virus persistence mechanisms in Africa and identifying risk situations, it proposes avenues for targeting surveillance and control strategies and thereby making them more efficient."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">In 2006, the detection of the avian influenza (flu) H5N1 virus in Africa caused great concern: the virus could spread to the whole continent, and then be reintroduced to Europe by migratory birds. Epidemiological surveillance programmes were set up and national mechanisms strengthened with the support of international organisations. At the same time, research programmes were launched to describe and understand the virus transmission processes in Africa, and to assess the risks. Among these programmes, the GRIPAVI project is aimed at characterising the circulation of avian influenza viruses and Newcastle disease in both wild birds and domestic poultry. It shows that the African continent is not free from risk and that vigilance should continue. By specifying the virus persistence mechanisms in Africa and identifying risk situations, it proposes avenues for targeting surveillance and control strategies and thereby making them more efficient.